Language Realizations of Dispreferred Social Acts in Intimate Relationship: a conversation analysis on the Lion King Movie - Sari, Dinda Anggi Novita; Sukmaantara, I Putu; Ariani, Musli (EFL Education Journal, 2016)
This article investigates the language realizations of dispreferred social acts from an animation movie called the Lion King (1994) used a model how English was used to express dispreferred social acts naturally. Descriptivequalitative research design was usedto describe the phenomena about dispreferred social acts. This research qualitatively generates the narrative data about he realizations of dispreferred social acts in the movie that were performed in mitigated and unmitigated forms. The research findings showed that the movie characters mitigated the form of the language realizations of dispreferred social acts to maintain social relationship. Unless their relationship was established, they sometimes express their intimate expressions directly without mitigation. Therefore, teachers should use the mitigated form of English to appear polite.